Development of Plaque Assay for Chilean Infectious Salmon Anaemia Virus, Application for Virus Purification and Titration in Salmon Ask Cells - Spencer-Ossa, E; Cortez-San Martin, M; Toro-Ascuy, D; Cottet-Bustamante, L (Blackwell Publishing Ltd, 2014)
Sin Resumen Disponible